Can the digital economy help reduce agricultural carbon emissions? An empirical test based on the moderated mediating effect model - Xu, Xiaodong; Wang, Shuo; Qin, Xutian; Han, Yufei (Frontiers in Sustainable Food Systems, 2024)
Considering agriculture's substantial carbon emissions, it is essential to examine how the digital economy can stimulate green innovation and low-carbon development by impacting these emissions. This article employs panel data from 31 provinces in China, covering the period from 2011 to 2020, to empirically analyze the effects of digital economy development on agricultural carbon emissions. The analysis utilizes the mediating pathway of agricultural green total factor productivity, while also considering the regulatory impact of green finance. The results indicate that: (1)Agricultural green total factor productivity has a partial mediating effect in the impact of the digital economy on agricultural carbon emissions, and green finance has a negative regulatory effect. (2)Green finance positively regulates the inhibitory effect of agricultural green total factor productivity on agricultural carbon emissions.(3)The development of the digital economy can inhibit agricultural carbon emissions, and this negative inhibitory effect follows a "U" shape. Our research offers a scientific foundation for the promotion of green and low-carbon development within Chinese agriculture, while also providing valuable references and insights for the global 1